The Effect of Applying the Learning Model Problem Based Learning Assisted Method Polya on Reasoning Ability and Solving Mathematics Story Problems in Students Grade IV Kasmaran Primary School - Stephanie Prisca Dewi; Ristiana Dyah Purwandari (Proceedings Series on Social Sciences & Humanities, 2025)
This study aims to determine the effect of PBL model learning assisted by the Polya method on improving mathematical reasoning and problem solving skills of fourth grade students of SD Negeri Kasmaran in the 2023/2024 academic year. This research uses a quantitative research approach, with an associative research type (relationship), and uses quantitative analysis methods (data in the form of numbers). Data on mathematical reasoning and problem solving skills were collected through observation using an assessment instrument in the form of a rubric. The sample in this study totalled 46 students. The research data were processed using simple linear regression test with the results for the effect of PBL model learning assisted by Polya method on mathematical reasoning skills tcount 2.478 and ttabel 2.015 means tcount > ttabel . For the effect of PBL model learning assisted by Polya method on problem solving skills tcount = 2.902 and ttabel = 2.776, means tcount 2.902 > ttabel 2.015. Based on the results of this study, it shows that there is an effect of PBL model learning assisted by Polya method on mathematical reasoning ability and problem solving ability of fourth grade students of SD Negeri Kasmaran in the 2022/2023 academic year.